Attitudes towards the implementation of universal umbilical artery lactate analysis in a South African district hospital. Issue 1 (December 2016) - Allanson, Emma; Grobicki, Kate; Pattinson, Robert; Dickinson, Jan
Abstract Background Of the 5.54 million stillbirths and neonatal deaths occurring globally each year, a significant amount of these occur in the setting of inadequate intrapartum care. The introduction of universal umbilical artery lactate (UA) measurements in this setting may improve outcomes by providing an objective measurement of quality of care and stimulating case reflection, audit, and practice change. It is important that consideration is given to the barriers and facilitators to implementing this tool outside of a research setting. Methods During the period 16/11/2014 -13/01/2015, we conducted a training course in cardiotocograph (CTG) interpretation, fetal physiology, and the sampling and analysing of UA lactate, with a pre and post questionnaire aimed at assessing the barriers and facilitators to the introduction of universal UA lactate in a district hospital in the Eastern Cape, South Africa. Results Thirty-five pre-training questionnaires available (overall response rate 95 %) and 22 post training questionnaires (response rate 63 %) were available for analysis. Prior to training, the majority gave positive responses (strongly agree or agree) that measuring UA lactate assists neonatal care, is protective for staff medicolegally, and improves opportunities for audit and teaching of maternity practice (n  = 33, 30, 32; 94.4 %, 85.7 %, 91.4 % respectively). Respondents remained positive about the benefits post training. An increased workload on medical or midwifery staff was less likely to be seen as barrier following training (71 vs. 38.9 % positive response, p  = 0.038). A higher rate of respondents felt that expense and lack of equipment were likely to be barriers after completing training, although this wasn't significant. There was a trend towards lack of time and expertise being less likely to be seen as barriers post training. Conclusion The majority of participants providing intrapartum care in this setting are positive about the role of universal UA lactate analysis and the potential benefits it provides. Training aids in overcoming some of the perceived barriers to implementation of universal UA lactate analysis.